Disease progression and mortality with untreated HIV infection: evidence synthesis of HIV seroconverter cohorts, antiretroviral treatment clinical cohorts, and population-based survey data - Glaubius,R; Kothegal,N; Birhanu,S; Jonnalagadda,S; Mahiane,SG; Johnson,LF; Brown,T; Stover,J; Mangal,T; Pantazis,N; Eaton,J (Journal of the International AIDS Society, 2021)
Background: Model-based estimates of key HIV indicators depend on past epidemic trends that arederived based on assumptions about HIV disease progression and mortality in the absence ofantiretroviral treatment (ART). Population-based HIV Impact Assessment (PHIA) household surveysconducted between 2015 and 2018 found substantial numbers of respondents living with untreated HIVinfection. CD4 cell counts measured in these individuals provide novel information to estimate HIVdisease progression and mortality rates off ART.Methods: We used Bayesian multi-parameter evidence synthesis to combine data on i) cross-sectionalCD4 cell counts among untreated adults living with HIV from ten PHIA surveys, ii) survival after HIVseroconversion in East African seroconverter cohorts, and iii) post-seroconversion CD4 counts and iv)mortality rates by CD4 count predominantly from European, North American, and Australianseroconverter cohorts. We used Incremental Mixture Importance Sampling to estimate HIV naturalhistory and ART uptake parameters used in the Spectrum software. We validated modeled trends in CD4count at ART initiation against ART initiator cohorts in sub-Saharan Africa.Results: Median untreated HIV survival decreased with increasing age at seroconversion, from 12.5years (95% credible interval [CrI]: 12.1-12.7) at ages 15-24 to 7.2 years (95% CrI: 7.1-7.7) at ages 45-54.Older age was associated with lower initial CD4 counts, faster CD4 count decline and higher HIV-relatedmortality rates. Our estimates suggested a weaker association between ART uptake and HIV-relatedmortality rates than previously assumed in Spectrum. Modeled CD4 counts in untreated people livingwith HIV matched recent household survey data well, though some intercountry variation in frequenciesof CD4 counts above 500 cells/mm3 was not explained. Trends in CD4 counts at ART initiation werecomparable to data from ART initiator cohorts. An alternate model that stratified progression andmortality rates by sex di